Testing the Automatic Voltage Regulators of Ship Synchronous Generators Using Hardware-in-the-Loop Technology - Dariusz Tarnapowicz; Tymoteusz Zaleski; Zbigniew Matuszak; Marek Jaskiewicz; Seweryn Sawicki (Energies)
In marine systems, autonomous power generation unit sets play an important (main) function, and the Automatic Voltage Regulator (AVR) is a part of the excitation system of a synchronous generator that is difficult to test, repair, and adjust by the Electro Technical Officer (ETO) and marine automation services. Typically, testing of the AVR on ships is carried out on installed AVRs in an operating generator, which creates significant challenges. Under operating conditions, achieving various generator operating states is practically impossible. In this article, the authors present a solution that replaces traditional AVR testing by using Hardware-in-the-Loop (HiL) technology, allowing for full diagnostics. Testing the AVR in a loop allowed verification of its performance without a real generator, which is simulated in real time. The possibility of diagnosing the AVR under different standalone generator conditions (dynamic load changes and load character changes) was presented. Test scenarios were carried out in real time on a sample AVR from LXCOS V1.4.5.2 and the HiL simulator from Speedgoat. The solution proposed by the authors in the article enables effective diagnostics of the AVR with high practicality and low costs.